WHAT WE CAN CHANGE IS OURSELVES: Experiences of Women Leaders In Religious-Based Higher Education Organizations - Hadiwirawan, Olivia; Luvian, Enrica; Kurniali, Kenly (PALASTREN: Jurnal Studi Gender, 2023)
The number of women leaders in Indonesia is considered to be low, even among other countries in ASEAN. Increasing the number of women’s participation in areas that have been dominated by men is often seen as a useful strategy to increase the number of women leaders. This solution was based on the pipeline metaphor which assumed that the numbers of women’s participation are equal to the numbers of women’s leaders in the future.  Unfortunately, this solution will usually reduce the complexity of women's progress toward leadership into a single narration that women lack leadership skills. This research aims to explore the experiences of women leaders in faith-based higher education organizations. A descriptive phenomenological was used to illustrate the dynamics of women leaders' subjective interactions. Findings show that women are dedicated leaders, they evaluate their leadership and have religious values to guide them in their leadership process. In addition, organizational culture based on religious values and the expected gender roles can help women in their path toward leadership. This study implies that researchers need to be aware of gender biases in constructing leadership and create a model of women's leadership which acknowledges and overcomes those gender biases.